Response of Students to Arabic Learning Curriculum in Pondok Pesantren - Putra, Noprio Rahma (Tanwir Arabiyyah: Arabic as Foreign Language Journal, 2022)
Arabic learning curriculum in the pesantren becomes a dilemma because learning resources are mainly used in Arabic, so the presence of an Arabic learning curriculum seems to undermine the ability of students to use Arabic. This study aimed to describe the responses of students on the Arabic learning curriculum with its various aspects. This study was conducted with a quantitative approach and the data collected were on a Likert scale on 68 people. Based on the results, according to the students, the Arabic learning curriculum in the pesantren students is not so important considering that various learning resources have used Arabic. The role of the Arabic learning curriculum in the pesantren, especially in the conservative aspect, has been accommodated in the pesantren curriculum, while from the creative aspect, students are of the view that the Arabic learning curriculum has a role to develop creativity, especially from the communication aspect. On the other hand, the perception of students towards the Arabic learning curriculum in the pesantren contains critical values for cultural development in accordance with the Indonesian character.